Komparasi Rencana Pelaksanaan Pembelajaran (RPP) Berdasarkan Kurikulum 2013 dengan di Kurikulum Merdeka Belajar - Shinta S; Munadira M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
One of the factors that supports a teacher’s success in the learning process is the availability of instructional tools that can be used by teachers. A good and proper learning process should begin with the preparation of a learning implementation plan. This study aims to identify the differences between learning implementation plans in the 2013 Curriculum and those in the Merdeka Belajar (Independent Learning) Curriculum. The research methodology employed is a Systematic Literature Review. Differences in the Learning Implementation Plan (RPP) between the 2013 Curriculum and the Merdeka Curriculum are found in several components, such as terminology. In the 2013 Curriculum, the term RPP is still used, whereas in the Merdeka Curriculum it is replaced by the term teaching module. In terms of learning outcomes, the 2013 Curriculum uses the terms Core Competencies (KI) and Basic Competencies (KD), while the Merdeka Curriculum divides learning outcomes into several phases: Phase A (Grades 1 and 2), Phase B (Grades 3 and 4), Phase C (Grades 5 and 6), Phase D (Grades 7, 8, and 9), Phase E (Grade 10), and Phase F (Grades 11 and 12). Furthermore, assessment in the RPP of the 2013 Curriculum still applies formative and summative assessments that evaluate students’ cognitive, affective, and psychomotor aspects, whereas the Merdeka Curriculum uses Minimum Competency Assessment and additional assessment for strengthening the Pancasila Student Profile.